Integrasi Umat, Kemiskinan, dan Radikalisme dalam Jamaah Tablighi di Indonesia - Hamdi, Saipul (Jurnal Review Politik, 2017)
This article examines the Tablighi’s effort for integrating ummah in their da’wah practices. Tablighi’s da’wah does not only carry on ritual and worship, but also humanitarian and social mission to strengthening peace building, equality and harmony for all. Tablighi applies the open system that welcome to all groups without considering their social background including ideology, ethnicity, culture, language, madhab or sects. Tablighi emphasizes to unfold religious differences, which have accused social distance and separation among Muslim groups. This endeavour effect the Tablighi’s rank of attraction for outsider to engage in Tablighi da’wah following flexible negotiation of previous socio-religious identity. How Tablighi integrates the ummah and manages differences will be demonstrated further in the article. Tablighi proselytizing pattern that requires all member to move from one place to another khuruj fi sabilillah for long term has major impact to economic stability that may impoverished them and the family has brought the specific question how they understand poverty, how far they aware of and how they overcome this issue. Meanwhile in global context Tablighi has been suspected as part of international terrorist group network following the suicide bombing attacks in England, Spain and France, therefore this article also elucidates Indonesian Tablighi involvement in radicalism and terrorism activities, and its network to global terrorist group. Tablighi’s appearance such as maintaining long beard, wearing robe, turban, and full hijab for their woman has been one factor that emerges social suspicion in public. As the result, Tablighi claimed as part of terrorist, so the article outlines the verification from Tablighi if that suspicion is true or not particularly in Indonesian context.